CAN MEASURES OF VASCULAR COMPLIANCE BE USED TO PREDICT SARCOPENIA IN THE ELDERLY?. (June 2018) - Kirkham, F.A.; Bunting, E.; Fantin, F.; Kern, F.; Zamboni, M.; Rajkumar, C.
Abstract : Objective: Sarcopenia, the loss of lean mass and increase in fat mass with age, is associated with increased cardiovascular risk. Sarcopenic muscle atrophy has been correlated with arterial stiffness (measured via brachial-ankle pulse wave velocity) in large-scale studies of predominately Asian patients. Our study investigated the correlation between sarcopenia and arterial stiffness in Caucasians, centring on the relationship between skeletal mass index (SMI) and the cardio-ankle vascular index (CAVI), to assess the use of CAVI in predicting sarcopenia. Design and method: 366 UK participants (177 male, 189 female, age 70.8 ± 7.9) had measurements of body composition and vascular compliance. Bioimpedance analysis (TANITA BC-418) was used to derive SMI, according to Janssen et al 1 . CAVI was measured using VaSera VS-1500N ® (Fukuda Denshi, Japan). Handgrip strength was measured with a dynamometer. Results: CAVI was significantly correlated with SMI (r = −0.285, p < 0.001), higher in females (r = −0.416, p < 0.001) than males (r = −0.214, p = 0.01). CAVI had the highest correlation with SMI from appendicular muscle (fat free mass in males – r = −0.253, p = 0.002, and predicted muscle mass in females – r = −0.436, p < 0.001). Using muscle mass, CAVI was significantly higher in sarcopenic (9.80) than non-sarcopenic individuals (8.98, p < 0.001). Using handgrip strength, sarcopenic individuals had significantly higher CAVI (9.53) than non-sarcopenic (9.10, p = 0.018). After adjustment for age, CAVI was a significant predictor of SMI in females (Beta = −0.332, p < 0.001) but not males. On nominal regression, CAVI was a significant predictor of the presence of moderate sarcopenia (odds ratio OR 1.49, 95% CI 1.04–2.14, p = 0.03) and, especially, severe sarcopenia (OR 1.87, 95% CI 1.26–276, p = 0.002) according to Janssen's criteria 1 . In females, CAVI predicted moderate sarcopenia with OR 1.74 (95% CI 1.08–2.78, p = 0.02) and severe sarcopenia with OR 2.74 (95% CI 1.52–4.92, p = 0.001). In males, CAVI became non-significant as a predictor of sarcopenia after adjustment for age. Conclusions: Indices of sarcopenia are independently associated with increased arterial stiffness, with higher correlation in females than males. Average CAVI assesses overall vascular compliance and may be a useful tool by which we can measure sarcopenia and its cardiovascular implications in older patients. Figure. No caption available.